Between the legal technique and the social question: the plural commitments of public defenders in Argentina - Ciocchini, Pablo Leandro (Crime, law and social change, 2023)
The criminal process in the Province of Buenos Aires has been affected by radical reforms in the last decades. Beginning with the complete replacement of the criminal procedure code in 1998 to the introduction of pre-trial hearings and simplified procedures for cases declared in flagrante delicto in 2004 the reforms have impacted more than legal procedures; they have changed the way judicial actors perceive themselves and their relations with the institution. Based on interviews with ten public defenders of the PBA this article offers an exploratory analysis on how public defenders’ perceptions have been impacted by those reforms and to what extent those internal changes have affected the internal dynamics of the PD. Drawing from the sociology of Bernard Lahire and Laurent Thenevot we identify in the public defenders’ responses how these changes affected their personal commitments. Mapping those commitments allow us to describe the subjective folds of the PD through which it is possible to better understand the decisions of public defenders by considering the internalization they make of the judicial world and its relationship with the institutional context.